الضوابط القرآنية في معالجة الفكر الجمعي: دراسة موضوعية في المنهج والمقاصد: Qur’anic Guidelines for Regulating Collective Thought: A Thematic Study of Method and Maqāṣid - Elatrash, Radwan Jamal Yousef; Zakariyah, Habeebullah; Faris, Waleed Fekry (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث تهدف هذه الدراسة إلى بيان الضوابط القرآنية التي أرساها الوحي لمعالجة ظاهرة الفكر الجمعي (Collective Mind)، والتي يُقصد بها خضوع الفرد لآراء الجماعة وتبني قراراتها دون تمحيص أو دليل، فيما يُعرف أيضًا بـ"فكر القطيع" (herd mentality). وقد اعتمد القرآن الكريم في معالجته لهذه الظاهرة على منهجية متكاملة تقوم على إرساء أسس التفكير الحر القائم على الدليل، وتوجيه الأفراد والمجتمعات نحو إعمال العقل بالتأمل والتدبر، من خلال الإكثار من المحاورات والمجادلات ورد التساؤلات، لتصحيح المسار وحماية الإنسان من التقليد الأعمى والانقياد وراء الشائع لمجرد انتشاره. يعتمد البحث على المنهج الاستقرائي لجمع الآيات القرآنية ذات الصلة بالفكر الجمعي واستخلاص ضوابطه المنظمة، وعلى المنهج التحليلي لبيان دلالاتها ومقاصدها في سياقاتها المختلفة. وتوصلت الدراسة إلى أن القرآن الكريم قد وضع جملة من الضوابط الفكرية والأخلاقية لضبط التفاعل الجمعي، مؤسسًا بذلك منهجية واضحة لتحويله من فكر سلبي مثبط إلى وعي مجتمعي إيجابي (Social consciousness) ينهض بالأفراد والمجتمعات. ABSTRACT This study aims to present the Qur’anic regulations established by divine revelation to address the phenomenon of the collective mind (Collective Mind), which refers to an individual’s submission to the opinions of the group and the adoption of its decisions without scrutiny or evidence—a phenomenon also known as “herd mentality.” In its treatment of this phenomenon, the Qur’an adopts an integrated methodology based on establishing the principles of free thinking grounded in evidence and directing individuals and societies toward engaging the intellect through reflection and contemplation. This is achieved through the frequent use of dialogues, debates, and responses to questions, with the goal of correcting courses and protecting individuals from blind imitation and following what is widespread merely because of its popularity. The study employs the inductive method to collect Qur’anic verses related to the collective mind and to derive its governing regulations, and the analytical method to clarify their meanings and purposes in various contexts. The study concludes that the Qur’an has laid down a set of intellectual and moral regulations to guide collective interaction, thereby establishing a clear methodology to transform it from a negative and discouraging mindset into a positive social consciousness that uplifts individuals and societies.